Reynolds number effects on flow topology above blunt-edge delta wing VFE-2 configurations - Said, Mazuriah (2015)
This paper discusses further the effects of Reynolds number, angle of attack and leading edge bluntness on the flow topology above delta wing VFE-2 configurations. In this project two delta wing models differentiated by its leading edge radius to the mean aerodynamics chord ratio of 0.15 and 0.3, namely the medium and large radius wing, were tested in Universiti Teknologi Malaysia wind tunnel. The relationship between the leading edge primary vortex and the occurrence of a secondary vortex called the inner vortex on the round-edged delta wings are discussed. The effects of leading edge bluntness, angle of attack and Reynolds number on both vortex systems are further discussed in this paper. The tests in this study were performed at speeds of 18.0 m/s, 36.1 m/s, and 54.2 m/s representing Reynolds numbers of 1×106, 2×106 and 3×106 and based on the mean aerodynamic chord. Two measurement techniques were employed on the models i.e. steady force balance and surface pressure data. The current experiments showed that an increase in leading edge bluntness and Reynolds number can delay the formation of the primary vortex towards the aft portions of the wing.